Upaya Menjaga Akuntabilitas Pertukaran Data dengan Teknologi Informasi Multiprotocol Label Switching - Ariefah Rachmawati (The Winners, 2007)
Data communication network, part of the information technology, becomes so important in communicating information and transferring data. Most companies in the world, including companies operating in Indonesia, have used data communication networking technology for their day-to-day operation. However, transferring data through network has some security problems. Therefore, accountants should be familiar with and have knowledge about it in order to ensure high quality work that they provide. Based on IETF – Internet Engineering Task Force a (RFC (Request for Comment)-3031), it is stailea that information technology used to communicate and transfer information as well as data should be efficient and safe.  Multiprotocols Label Switching (MPLS) is a new technology used in virtual private network is one of the solutions in making data transfer efficient and safe.